Abstract markings in the rock art of Iran: relative dating and possible function of the markings. (2nd April 2020) - Karimi, Ebrahim
ABSTRACT: Although large number of rock art sites have been identified in Iran, our knowledge about dating of this art has remained very limited. This paper reviews the previous works on dating rock art of Iran. Moreover, using relative dating approaches, the paper discusses possible dating for abstract markings in the rock art of the country. Some petroglyphs carved on an ancient bas-relief and on the walls of ancient constructions of the known age assist us to put some abstract depictions in a historic, particularly, an 'Islamic' context. In addition, using ethnographic evidence, the paper discusses the possible function of abstract motifs in the rock art of Iran.